Human capital and growth : the recovered role of educational systems - Dessus, Sébastien (Policy research working paper, 2001)
When investments in education in developing countries do not produce higher growth, the problem may be the quality of the schooling, of the education infrastructure, of the initial endowment in human capital, and of the system's ability to equitably distribute educational services. The consensus to support and emphasize public primary education for all (rather than secondary education for the few), typically found in the most egalitarian societies, is most likely to increase the contribution of human capital accumulation to growth